EDUCATION ON THE USE OF HYPERTENSION MEDICATIONS IN KALIBARU RW.10, CILINCING DISTRICT, JAKARTA UTARA - Astiani, Rangki; Sari, Dini Permata; Kristina, Eka (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2024)
Hypertension is a disease that many Indonesian people suffer from. Medicines play an important role in health care, but their inappropriate use can pose risks to health and the environment, especially the use of hypertension drugs. To overcome this problem, a counseling and socialization program on the use of hypertension drugs is needed to increase public knowledge. The aim of this activity is to provide education about the classification of drugs, as well as how to obtain, use, store and dispose of drugs correctly, in order to reduce misuse when using hypertension drugs. The implementation method involves counseling and distributing brochures in August 2024 in Kalibaru Village RW 10, Cilincing District, North Jakarta. The activity was carried out by socializing the material using PowerPoint for 100 minutes, followed by an interactive discussion and question and answer session. The material presented includes the use of hypertension drugs, how to use them, and avoiding drug interactions, as well as the correct procedures for managing hypertension drugs. The results of the activity showed active participation from the community in discussions and questions and answers. Participants' knowledge increased regarding the proper use of hypertension medication, appropriate storage and safe disposal. Interactive discussions revealed participants' curiosity and awareness of the importance of correct hypertension medication management. This activity succeeded in achieving its goal, increasing public understanding about hypertension therapy, and it is hoped that it can help prevent drug use errors in the family environment.